Investigation of phase-contrast magnetic resonance imaging underestimation of turbulent flow through the aortic valve phantom: experimental and computational study using lattice Boltzmann method - Fučík, Radek; Galabov, Radek; Pauš, Petr; Eichler, Pavel; Klinkovský, Jakub; Straka, Robert; Tintěra, Jaroslav; Chabiniok, Radomír (Magma, 2020)
OBJECTIVE: The accuracy of phase-contrast magnetic resonance imaging (PC-MRI) measurement is investigated using a computational fluid dynamics (CFD) model with the objective to determine the magnitude of the flow underestimation due to turbulence behind a narrowed valve in a phantom experiment. MATERIALS AND METHODS: An acrylic stationary flow phantom is used with three insertable plates mimicking aortic valvular stenoses of varying degrees. Positive and negative horizontal fluxes are measured at equidistant slices using standard PC-MRI sequences by 1.5T and 3T systems. The CFD model is based on the 3D lattice Boltzmann method (LBM). The experimental and simulated data are compared using the Bland-Altman-derived limits of agreement. Based on the LBM results, the turbulence is quantified and confronted with the level of flow underestimation. RESULTS: LBM gives comparable results to PC-MRI for valves up to moderate stenosis on both field strengths. The flow magnitude through a severely stenotic valve was underestimated due to signal void in the regions of turbulent flow behind the valve, consistently with the level of quantified turbulence intensity. DISCUSSION: Flow measured by PC-MRI is affected by noise and turbulence. LBM can simulate turbulent flow efficiently and accurately, it has therefore the potential to improve clinical interpretation of PC-MRI.
Keywords: Blood Flow Velocity; aortální stenóza; magnetická rezonanční tomografie; lidé; fantomy radiodiagnostické; Aortic Valve Stenosis; aortální chlopeň; Magnetic Resonance Imaging; Humans; Aortic Valve; rychlost toku krve; Phantoms, Imaging